The Amino Acid Profile in Seminal Plasma of Normozoospermic Men: A Correlation Analysis with Spermiogram Parameters and Total Antioxidant Capacity - Amirjannati, Naser; Henkel, Ralf; Hosseini, Elham; Choopanian, Peyman; Moghadasfar, Hanieh; Arjmand, Babak; Asgharpour Sarouey, Lima; Haji Parvaneh, Azadeh; Gilany, Kambiz (Journal of Reproduction & Infertility, 2023)
Background: Male infertility is usually determined by the manual evaluation of the semen, namely the standard semen analysis. It is currently impossible to predict sperm fertilizing ability based on the semen analysis alone. Therefore, a more sensitive and selective diagnosis tool is required. Methods: Twelve fresh semen samples were collected from fertile volunteers attending the Avicenna Fertility Center (Tehran, Iran). The seminal plasma (SP) was prepared and subjected to liquid chromatography-tandem mass spectrometry (LC-MS/MS), and the total antioxidant capacity (TAC) was analysis. Thirty-four amino acids including essential amino acids (EAA), non-essential amino acids (NEAA), and non-proteinogenic amino acids (NPAA) relative concentration were determined, and the correlation between their concentration with spermiogram parameters and TAC of the SP was analyzed. Results: Significant positive correlations have been found between selected amino acids with the motility (Met and Gln, rs=0.92; Cys, rs=0.72; and Asn, rs=0.82), normal sperm morphology (Met, rs=0.92; Cys, rs=0.72; Glu, rs=0.92; and Asn, rs=0.82), and sperm concentration (Trp, Phe, and Ala). In contrast, several AAs, including Gly, Ser, and Ile showed negative correlations with sperm concentration (rs=-0.93, r=-0.92, and r=-0.89, respectively). Furthermore, TAC showed a positive association only with Tyr (rs=0.79). Conclusion: The strong positive/negative correlations between the seminal metabolic signature and spermiogram demonstrate the significance of determining metabolite levels under normal conditions for normal sperm functions. Combining the metabolome with the clinical characteristics of semen would enable clinicians to look beyond biomarkers toward the clinical interpretation of seminal parameters to explain the biological basis of sperm pathology.